Stainless steel ring strengthened removable dowel bar connection system: Effect of key parameters and design recommendations. (October 2022) - Guo, Jiachen; Chan, Tak-Ming
Abstract: This paper numerically studies key parameters which affect the structural performance of the stainless steel ring strengthened removable dowel bar connection system. Finite element models were firstly validated against experimental test results in terms of the failure mode and load–deflection relationship. Then validated models were used to carry out the parametric investigation. The dowel bar diameter, the stainless steel ring length as well as the stainless steel ring thickness were studied with 90 generated models. According to the finite element analysis results, it was found that the vertical stiffness and ultimate load were enhanced with the increase of the dowel bar diameter. And the application of the stainless steel ring significantly relieved the compressive stress concentration at joint surface due to the expanded contact area. Close relationships were then observed between the ultimate load and the stainless steel ring thickness and length, respectively. Empirical equations were also derived to predict the ultimate load under the ultimate limit state (ULS). Meanwhile, under 20 kN service limit state (SLS), a close relationship was also found between the maximum compressive stress of concrete and the external diameter of the stainless steel ring. Through this two-stage design, the stainless steel ring strengthened removable dowel bar connection system will be more durable and reliable.